These are the Avengers - Macri, Thomas (New York : Marvel, 2012)
Introduces the six superheroes that make up the Avengers.
"Based on the Marvel comic book series The Mighty Avengers."
Cover title: The mighty Avengers
1.1
Preschool
Preschool
340L
Keywords: Avengers (Fictitious characters) -- Juvenile fiction; Superheroes -- Juvenile fiction; Avengers (Fictitious characters) -- Fiction; Superheroes -- Fiction; Avengers (Fictional characters) -- Fiction; Superheroes -- Fiction; Readers (Elementary)